2008
DOI: 10.1080/03610730802271922
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in Tissue and Plasma Zinc Levels: Modulation by Exogenously Administered Melatonin

Abstract: Melatonin (MEL) is synthesized mainly in the pineal gland and derived from 5-hydroxytryptophan (5-HTP). Zinc (Zn) is one of the most important trace elements in the body. Zn and MEL levels are changed with aging. The aim of this study was to investigate the age-related changes of tissue and plasma Zn levels and effect of MEL administration on these parameters. Male wistar rats received for 3 weeks subcutaneous injection of MEL (10 mg/kg). Kidney and pancreas Zn levels in old rats were significantly lower than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Our findings do not preclude an alteration of the micronutrient content in the bone matrix; the addition of trace amounts of zinc [19], [20], [21], [22] or strontium [23], [24], [25] to bone matrix can improve fracture resistance and strength without affecting overall weight or total mineral content. Melatonin has been shown to affect absorption of micronutrients, including ions [26], [27] such as zinc [28], [29].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings do not preclude an alteration of the micronutrient content in the bone matrix; the addition of trace amounts of zinc [19], [20], [21], [22] or strontium [23], [24], [25] to bone matrix can improve fracture resistance and strength without affecting overall weight or total mineral content. Melatonin has been shown to affect absorption of micronutrients, including ions [26], [27] such as zinc [28], [29].…”
Section: Discussionmentioning
confidence: 99%
“…The strength of the dietary supplement lies in the rational combination of these three nutrients given the potent synergy between the effect of melatonin, magnesium, and zinc. 28,47 Moreover, the melatonin, magnesium, and zinc supplement conveyed in pear pulp appears to be safe. No significant unwanted side or adverse effects were observed in the treated group, as reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue levels of zinc and copper decrease with aging in animals [13][14][15], but previously no data has been available regarding animal or human vaginal tissues. However, in the human uterus (corpus) during menopause, copper levels were seen to rise as zinc levels fell [23].…”
Section: Discussionmentioning
confidence: 99%
“…Animal experiments revealed that zinc affects the extracellular matrix of the vagina. Also, in aging mice and rats, the tissue concentration of zinc and copper decreases [13][14][15]. Histological and histochemical pictures of vaginas from mice with a zinc-deficient diet look similar to ovariectomized animals.…”
Section: Introductionmentioning
confidence: 85%